The Relationship Between Knowledge and The Use of Health Supplements During The Pandemic Towards Non-Medical Students of Sanata Dharma University - Yosef Wijoyo (Fakultas Farmasi Universitas Setia Budi, 2024)
The World Health Organization (WHO) declared COVID-19 as a pandemic on 11 March 2020. Based on the data on the distribution of the development of Covid-19, the pandemic in Indonesia itself is still high. One of the efforts to prevent the spread of COVID-19 cases is by increasing the body's immune system. Consuming health supplements is one of the efforts to increase endurance because it has the function to maintain, improving and/or repairing health. This study aims to determine whether there is a relationship between knowledge and actions to use health supplements among non-health students at Sanata Dharma University. This study is a type of Analytical Observational research with a cross-sectional approach. The research instrument is a questionnaire that was distributed online through the Google Form platform. The sample in this study was 368 respondents. The Data analysis in this study uses descriptive statistical tests, normality tests, chi-square tests and simple linear regression tests. In respondents' knowledge of health supplements, 85.9% of 316 respondents fell into the